Răspuns:
Explicație pas cu pas:
Fie f(x)=ax+b (functia de gradul 1)
f(x-1)=a(x-1)+b=ax-a+b
->>f(x)+f(x-1)=ax+b+ax-a+b
->>f(x)+f(x-1)=2ax+2b-a
Dar f(X)+f(x-1)=3x+2 ->>> 3x+2=2ax+2b-a
->>>2a=3 si 2b-a=2
->>>a=[tex]\frac{3}{2}[/tex] ->>2b=2+[tex]\frac{3}{2}[/tex] |Inmultim cu 2 in ambele parti ->>4b=4+3->>4b=7->>b=[tex]\frac{7}{4}[/tex]
Deci f(x)=[tex]\frac{3x}{2}[/tex]+[tex]\frac{7}{4}[/tex]
k=4f([tex]\frac{1}{2}[/tex])
f([tex]\frac{1}{2}[/tex])=[tex]\frac{5}{2}[/tex]
->>k=4*[tex]\frac{5}{2}[/tex]
->>k=10